Engineering of Cassava Stem Cellulose As a Filler for Manufacturing Plastic Biodegradable - Febrianti, Tika; Septiriana, Irene; Ariyanto, Verananda Kusuma; Rizky, Renaldy (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Biodegradable plastic is intensely researched in recently years. Out of many findings, one good finding suggests that lignocellulosic may prove to be one of the most useful alternatives to renewable environmental friendly sources. Cassava stems contain a 56.86 % cellulose. Cellulose from lignocellulosic material has a great impact to strengthen the mechanical properties of biodegradable plastic. Because cellulose has strong and stiff properties, it can be used to produce plastic film. The addition of glycerol helps to reduce the stiff properties of plastic film. This research is purposed to improve the use of cellulose from cassava stems to be a raw material of biodegradable plastic production. There are three methods to produce plastic film: hydrolysis, delignification, and casting of plastic film. IR spectra of biodegradable plastic results a cellulose and chitosan bonding because it has an ester group at wave number 2213 cm-1. SEM analysis of the additional of glycerol cracks the surface of plastic. Degradation analysis shows the use of cellulose increases the degradation rate for bioplastic by losing the mass of sample in three weeks. Tensile strength of bioplastic is not qualified with the specification of conventional polymer but it has good elongation. Therefore, there are necessarily additional materials to increase the tensile strength of bioplastic.